Powroty Adama Mickiewicza do Polski - Mikołaj Sokołowski (Pl.it)
The article points out the symbolic consequences of the return of Adam Mickiewicz – the most important Polish romantic poet – to Poland in the period of the November Uprising (1831). His overly prolonged stay in the Greater Poland region, while the capital Warsaw collapsed under Russian force, was treated by various patriots as evidence of his betrayal of the Polish case. This stage of a great national debate on the moral attitude of the romantic writers ends with the solemn funeral of Mickiewicz at the royal Wawel Castle in 1890, when his body was transferred from the family grave in Montmorency (France). This funeral concludes the return of the poet Adam Mickiewicz to Poland and it makes of him a symbol of the independence of the Polish state.